THE INFLUENCE OF THE HABIT OF PLAYING ONLINE GAMES ON THE LEARNING - Ismail Lahay; Abdul Rahman Pakaya; Sudirman Sudirman (Gorontalo State University, 2023)
The objective of this research was to findout the effect of online gaming habits on student,s learning outcomes in class X of social sciences in economics subject at SMA Negeri 1 Tapa, Bone Bolango Regency, It employed a quantitative method with a sample of 66 students. At the sama time, the data analysis used in this research was a simple linear regression analysis assisted by IBM Statistics SPSS 26.0 program. The research findings signified that the variable of online gaming habits partially had a negatif and significant effect on students’ learning outcomes in class X of social Sciences at SMA Negeri 1 Tapa, the results of this research obtainet a coefficient of determination (R2) of 0.169, meaning that the effect of online gaming habbits variabel on students’ learning outcomes at SMA Negeri 1 Tapa was 16.9%. in contrast, the remaining 83.1% was affected by other variables that contribute to students’ learning outcomes at SMA Negeri 1 Tapa, which were not examinet in this research.